Medicine Meets Virtual Reality 19 : NextMed - Westwood, James D (IOS Press, 2014)
When treating their patients, physicians confront a living system that is astoundingly complex, with checks and balances that are incompletely understood, and sensitive to pain. Technologists, on the other hand, work with man-made objects within the less emotional domains of materials and mathematics, creating anew or building upon prior work as creativity inspires and economics allow. The former juggles individual makeup with personal histories and emotional ramifications; the latter can take a good outcome and multiply it with industrial production methods. To a programmer and a surgeon, for example, “crisis” and “success” necessarily imply very different scenarios.